Application of a real‐time polymerase chain reaction assay to the diagnosis of bovine ephemeral fever during an outbreak in New South Wales and northern Victoria in 2009–10. Issue 1 (January 2014) - Finlaison, DS; Read, AJ; Zhang, J; Paskin, R; Kirkland, PD
<x xml:space="preserve">Abstract</x> Objective To report the occurrence of an epizootic of bovine ephemeral fever (BEF) in New South Wales (NSW) and northern Victoria in 2009–10 and describe the application of a real‐time reverse transcription polymerase chain reaction (qRT‐PCR) assay during the outbreak. Procedures Whole‐blood samples from animals exhibiting clinical signs of BEF were requested from district veterinarians in NSW. In addition, samples were submitted from private practitioners in NSW and Victoria. In NSW, samples from animals showing acute clinical signs of BEF were tested using a qRT‐PCR assay. Serological testing for BEF diagnosis was undertaken as required. Virus isolation was performed on selected samples in which bovine ephemeral fever virus (BEFV) RNA was detected. Archival serum samples and mosquito homogenates were also tested for BEFV by qRT‐PCR. Results Accessions were received from 121 properties in NSW, with cases of BEF confirmed on 84 properties by qRT‐PCR and 20 properties by serology. In northern Victoria, BEF was confirmed on 25 properties based on serological testing. Screening of samples by qRT‐PCR enhanced the success of BEFV isolation. BEFV RNA was successfully detected in archival serum samples and a single mosquito homogenate. Conclusions The 2009–10 outbreak resulted in the most extensive transmission of BEFV in NSW and Victoria since 1995–96, and follows a smaller outbreak in summer‐autumn 2008. The use of qRT‐PCR for BEF diagnosis offers veterinarians and cattle owners rapid confirmation of infection (1–2 days) and provides 'real‐time' information about the presence of the disease in a district.